Getting started with Spring 5.0 - Karanam, Ranga Rao; Safari eBooks ([Place of publication not identified] : Packt, 2017)
"Spring 5.0 is due to arrive with a myriad of new and exciting features that will change the way we've used the framework so far. This video will show you this evolution--from solving the problems of testable applications to building distributed applications on the cloud. The video begins with an insight into the new features in Spring 5.0 and shows you how to build an application using Spring MVC. The advanced features of Spring Boot will be illustrated through powerful examples. We will be introduced to a JVM language that's quickly gaining popularity - Kotlin. Also, we will discuss how to set up a Kotlin project in Eclipse. By the end of the video, you will be equipped with the knowledge and best practices required to develop microservices with the Spring Framework."--Resource description page.
Title from title screen (viewed October 25, 2017).
Date of publication from resource description page.
Keywords: Spring (Software framework); Application program interfaces (Computer software); Electronic books